2013
DOI: 10.1016/j.fob.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a putative aspartic proteinase domain of the Mycobacterium tuberculosis cell surface antigen PE_PGRS16

Abstract: We report the crystal structure of the first prokaryotic aspartic proteinase-like domain identified in the genome of Mycobacterium tuberculosis. A search in the genomes of Mycobacterium species showed that the C-terminal domains of some of the PE family proteins contain two classic DT/SG motifs of aspartic proteinases with a low overall sequence similarity to HIV proteinase. The three-dimensional structure of one of them, Rv0977 (PE_PGRS16) of M. tuberculosis revealed the characteristic pepsin-fold and catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The first structure for a PE/PPE protein pair (PE25 III /PPE41 III ) was determined in 2006 (Strong et al ., ). The crystal structure of a putative enzymatic domain of PE_PGRS16 V was reported in 2013 (Barathy and Suguna, ), and two complete PE25 III /PPE41 III structures (in complex with EspG) only followed in 2014 (Ekiert and Cox, ; Korotkova et al ., ), underlining the inherently challenging nature of these proteins. The limited experimentally confirmed structural data impose limitations on the ability to predict the functional consequences of PE/PPE variability.…”
Section: Evolution and Variation Of The Pe/ppe Familiesmentioning
confidence: 99%
“…The first structure for a PE/PPE protein pair (PE25 III /PPE41 III ) was determined in 2006 (Strong et al ., ). The crystal structure of a putative enzymatic domain of PE_PGRS16 V was reported in 2013 (Barathy and Suguna, ), and two complete PE25 III /PPE41 III structures (in complex with EspG) only followed in 2014 (Ekiert and Cox, ; Korotkova et al ., ), underlining the inherently challenging nature of these proteins. The limited experimentally confirmed structural data impose limitations on the ability to predict the functional consequences of PE/PPE variability.…”
Section: Evolution and Variation Of The Pe/ppe Familiesmentioning
confidence: 99%
“…These secreted proteins are named after several highly conserved residues in their characteristic N‐terminal motifs: proline‐glutamic acid (PE) and proline‐proline‐glutamic acid (PPE) (Cole et al ., ). The C‐terminal domains of both PE and PPE proteins can be extremely long and some carry functional domains such as lipase (Deb et al ., ; Mishra et al ., ; Daleke et al ., ), aspartic protease (Barathy and Suguna, ) and serine hydrolase (Sultana et al ., 2011; 2013) domains. Although the precise function of these proteins is largely unknown, it has been demonstrated that various PE/PPE proteins are associated with virulence and persistence in the host (Sampson, ).…”
Section: Introductionmentioning
confidence: 99%
“…gordonae ) predicted to comprise the aspartic proteinase domain are shown in the supplementary data ( S2 Appendix ). This domain was reported in the PE_PGRS16 (Rv0977) protein and its three-dimensional crystal structure was solved (PDB_ID: 4EHC) [ 44 ]. The aspartic proteinase domain has low overall sequence similarity to HIV proteinase with a characteristic pepsin-fold and catalytic site architecture.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent experiments confirmed that the PE-PPE domain of PE16 (Rv1430) exhibited esterase activity [ 43 ]. Recently, Bharathy and Suguna identified and solved the three-dimensional crystal structure of an aspartic proteinase-like domain observed in the C-terminal region of the PE_PGRS16 (Rv0977) protein [ 44 ].…”
Section: Introductionmentioning
confidence: 99%